About the Efficiency of Jury Trial in Russia - SEMENTSOV, Vladimir A.; GLADYSHEVA, Olga V.; FEOKTISTOV, Maksim V. (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
There are reasons to the fact that jury trial is experiencing hard times in modern Russia. There are negative factors affecting the efficiency of jury trial, and it is proposed to exclude jury trial from the procedure of the criminal proceedings as unnecessarily complicated and costly form of the legal proceedings.